2008
DOI: 10.1080/13682820701839200
|View full text |Cite
|
Sign up to set email alerts
|

Language profiles of monolingual and bilingual Finnish preschool children at risk for language impairment

Abstract: Although a slight general cost of bilingualism was found in the language profile of the six-year olds in this study, a bilingual background was not associated with more severe language problems in the LI Risk Group. Thus, there would seem to be no need to shield language-impaired children from opportunities for dual language learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 20 publications
6
50
1
1
Order By: Relevance
“…Thus, although bilinguals had a similar performance to the ENI normative group, the results also point to the fact that bilingualism is an important variable that needs to be considered when in doing neuropsychological assessments. Similar results were found in the Westman et al (2008) study, in which 6-year-old Finnish-speaking monolinguals and Finnish-Swedish bilinguals were administered subtests from the Wechsler Primary and Preschool Scale of Intelligence-Revised and the NEPSY battery. Again, the findings highlighted a verbal cost for bilinguals on measures of (single-language) vocabulary and sentence repetition, with no other significant differences.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Thus, although bilinguals had a similar performance to the ENI normative group, the results also point to the fact that bilingualism is an important variable that needs to be considered when in doing neuropsychological assessments. Similar results were found in the Westman et al (2008) study, in which 6-year-old Finnish-speaking monolinguals and Finnish-Swedish bilinguals were administered subtests from the Wechsler Primary and Preschool Scale of Intelligence-Revised and the NEPSY battery. Again, the findings highlighted a verbal cost for bilinguals on measures of (single-language) vocabulary and sentence repetition, with no other significant differences.…”
Section: Resultssupporting
confidence: 84%
“…Given that neuropsychological tests can be used for the purposes of classifying children, providing diagnosis or treatment, it is important to get the measurement right and consider the factors that might impact performance, such as the experience of speaking two languages. To address this issue, three of the studies included in the present review examined bilingual children's performance on neuropsychological assessments in the United States (Rosselli et al, 2010), United Kingdom (Garratt & Kelly, 2008) and Finland (Westman, Korkman, Mickos, & Byring, 2008). …”
Section: Resultsmentioning
confidence: 99%
“…Research documents that children can effectively learn two languages simultaneously, regardless of their being normal-learning or developmentally challenged (Dufresne & Masny, 2006; Moore & Pérez-Méndez, 2006; Paradis, Genesee & Crago, 2011; Rowe, 2008; Westman, Korkman, Mickos, & Byring, 2008). This is consistent with participants’ statements that the presence of a developmental delay does not preclude speaking two languages.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have observed poorer oral language capacities in bilingual compared to monolingual children with SLI (Orgassa and Weerman, 2008;Westman, Korkman, Mickos, & Byring, 2008). However, other studies have failed to observe differences between the oral abilities of bilingual and monolingual children with SLI (Rothweiler, Chilla, & Clahsen, 2012;Windsor, Kohnert, Lobitz, & Pham, 2010) so evidence regarding this possibility is still inconclusive.…”
Section: Discussionmentioning
confidence: 97%